On the law applicable to detrimental acts - Torralba Mendiola, Elisa (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
In its judgment in Case C-73/20, the CJEU rules once again on the interpretation of article 13 of Regulation 1346/2000 on Insolvency Proceedings (article 16 of Regulation 848/2015, currently in force), this time in conjunction with article 12 of Regulation 593/2008, on the law applicable to contractual obligations. The CJEU’s conclusion ensures compliance with the objectives of both regulatory texts, guaranteeing legal certainty for those who benefited from the harmful act and acted in good faith.